Livestock, gender, and agency amid conflict in Ethiopia - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The Hybrid Research and Policy Conference on Livestock, Gender, and Agency Amid Conflict in Ethiopia, held on December 11, 2024, at the ILRI Campus in Addis Ababa and online, brought together a diverse group of policymakers, researchers, and development practitioners. The event was jointly organized by CGIAR Research Initiatives (NPS) and several key research institutes including, IFPRI, ILRI, and PSI.